Chemsex and new HIV diagnosis in gay, bisexual and other men who have sex with men attending sexual health clinics. Issue 7 (22nd May 2018) - Pakianathan, M; Whittaker, W; Lee, MJ; Avery, J; Green, S; Nathan, B; Hegazi, A
Abstract : Objectives: The aim of the study was to analyse associations between chemsex and new HIV and sexually transmitted infection (STI) diagnoses among gay, bisexual and other men who have sex with men (GBMSM) accessing sexual health clinics. Methods: A retrospective case note review was carried out for all GBMSM attending two London sexual health clinics between 1 June 2014 and 31 July 2015. Results: Chemsex status was documented for 1734 of 1840 patients. Overall, 27.1% ( n = 463) disclosed current recreational drug use, of whom 286 (16.5%) disclosed chemsex participation and 74 of 409 (18.1%) injected drugs. GBMSM who were already HIV positive were more likely to disclose chemsex participation [adjusted odds ratio (AOR) 2.55; 95% confidence interval (CI) 1.89–3.44; P < 0.001]. Those disclosing chemsex participation had higher odds of being newly diagnosed with HIV infection (AOR 5.06; 95% CI 2.56–10.02; P < 0.001), acute bacterial STIs (AOR 3.94; 95% CI 3.00–5.17; P < 0.001), rectal STIs (AOR 4.45; 95% CI 3.37–6.06; P < 0.001) and hepatitis C (AOR 9.16; 95% CI 2.31–36.27; P = 0.002). HIV‐negative chemsex participants were also more likely to have accessed post‐exposure prophylaxis for HIV in the study period and to report sex with a discordant HIV‐ or hepatitis C virus‐infected partner ( P < 0.001). Conclusions: Chemsex disclosure in sexual health settings is associated with higher rates of STI diagnoses, including HIV infection and hepatitis C. GBMSM attending sexual health services should therefore be assessed for chemsex participation and disclosure should prompt health promotion, harm minimization and wellbeing interventions.